Additions to the list of polonisms in the 17th century Russian Chancellery Language - Garbul, Liudmila Pavlovna (Slavistica Vilnensis, 2019)
The article examines the history of the four words found in the Muscovite diplomatic correspondence: mevati ‘to have’, menovati ‘to call, to name’, metsja ‘to feel yourself; to live’, meškaniec ‘inhabitant’. The author aims at proving that these words are lexical borrowings from Polish language. The study is based on a careful comparison of data of various types of dictionaries of the Russian, Belarusian, Ukrainian and Polish languages, which made it possible to prove the insincerity of these tokens in the Russian language and to establish the source of borrowing, as well as to identify the intermediary role written language of the Grand Duchy of Lithuania in Polish-Russian language contacts. The materials in this publication can be used to supplement and clarify the information of the etymological and historical dictionaries of the Slavic languages.
Keywords: lexical borrowing; Polonizm; chancellery language; diplomatic correspondence (documents); the written language of the Great Duchy of Lithuania